Prevalence and determinants of diabetes among older adults in Ghana. (December 2016) - Gatimu, Samwel; Milimo, Benson; Sebastian, Miguel
Abstract Background Diabetes is one of the leading non-communicable diseases in Africa, contributing to the increasing disease burden among the old adults. Thus, the aim of this study was to determine the prevalence and determinants of diabetes among adults aged 50 years and above in Ghana. Methods A cross sectional study based on data collected from Study of Ageing and Adult Health (SAGE) Wave 1 from 2007 to 2008. Data was collected from 5565 respondents of whom 4135 were aged 50+ years identified using a multistage stratified clusters design. Bivariate and hierarchical multivariable logistic regression models were used to examine the association of the determinants and diabetes. Results The weighted prevalence of diabetes among the adults aged 50 years and above in Ghana was 3.95% (95% Confidence Interval: 3.35–4.55) with the prevalence being insignificantly higher in females than males (2.16%, 95% CI: 1.69–2.76 vs. 1.73%, 95% CI: 1.28–2.33). Low level of physical activity (Adjusted Odds Ratio [AOR] 2.11, 95% CI: 1.21–3.69) and obesity (AOR 4.81, 95% CI: 1.92–12.0) were associated with increased odds of diabetes among women while old age (AOR 2.58, 95% CI: 1.29–5.18) and university (AOR 12.8, 95% CI: 4.20–39.1), secondary (AOR 3.61, 95% CI: 1.38–9.47) and primary education (AOR 2.71, 95% CI: 1.02–7.19) were associated with increased the odds of diabetes among men. Conclusion The prevalence of diabetes among old adults shows a similar trend with that of the general population. However, the prevalence may have been underestimated due to self-reporting and a high rate of undiagnosed diabetes. In addition, the determinants of diabetes among older adults are a clear indication of the need for diabetes prevention programme targeting the young people and that are gender specific to reduce the burden of diabetes at old age. Physical activity and nutrition should be emphasised in any prevention strategy.